English for Specific Purposes Teacher Education: Connecting, Collaborating and Developing Through the Use of Technology - Kakoulli-Constantinou, Elis (My University, 2022)
Technology has significantly influenced all fields of language pedagogy including English for Specific Purposes (ESP). Research in this area has been extensive with many studies focusing on the integration of different technology tools in the teaching and learning process (Kakoulli Constantinou & Papadima-Sophocleous, 2020). The exploration of the use of technology has become more intense after the COVID-19 pandemic. Nevertheless, research in the integration of technology in ESP teacher education is limited thus far. This paper aims at elaborating on the importance of using technology in ESP teacher education as reflected in the results of a technical action-research study which aimed at addressing the neglected need for ESP teacher education among a group of 24 language instructors from different parts of the world; this was achieved through the design and delivery of an online ESP teacher education programme and eventually the formulation of an online community, based on the theories of social constructivism (Detel, 2001) and connectivism (Siemens, 2005). Following the spiral processes of technical action research, the study unfolded in two cycles, each of which consisted of a series of processes and steps. The study employed a mixed-methods approach to data collection and analysis, even though the data collected were mainly qualitative. The results of the study showed, among other things, the importance of including technology in ESP teacher education both in the syllabus of ESP teacher education programmes and in the delivery of these programmes.
Keywords: English for Specific Purposes; Teacher Education; Social Constructivism; Connectivism